Superconducting transition edge bolometer for high-flux neutron detection - Mette Bybjerg Brock; Emil Visby Østergaard; Matteo Busi; Anders C. Wulff; Asger Bech Abrahamsen; Luise Theil Kuhn (Scientific Reports, 2023)
Abstract Needs for neutron detection and monitoring in high neutron flux environments are increasing in several different fields. A completely solid-state, current mode bolometric detector is constructed as a solid substrate transition edge sensor based on a high-T $$_c$$ c superconducting meander. The detector consists of four individual pixels of which three pixels include $${^{10}{\hbox {B}}_{4}\hbox {C}}$$ 10 B 4 C neutron absorption layers. The absorbed energy per neutron absorption reaction is modelled and compared to experimental data. The response of the tested detector is directly correlated to a cold neutron beam with a flux of $${1.8\times 10^{8}}\,{\hbox {n}/{\hbox {cm}}^2/\hbox {s}}$$ 1.8 × 10 8 n / cm 2 / s modulated by a slit. The signal is found to be an order of magnitude higher than the thermal background. The dynamics described by the temporal saturation constants is governed by a modulation frequency less than $${1}\hbox { Hz}$$ 1 Hz . The thermal response is dynamic and never fully saturates for $${50}\hbox { s}$$ 50 s exposures. The efficiency for this proof-of-principle design is 1–2%. Possibilities for optimization are identified, that will increase the efficiency to become comparable to existing solid boron-10 detectors. The existing detectors with event-based read-out have limited functionality in high flux environments. The superconducting bolometer described in this work using current-mode readout will pave the way for high flux applications.